2017
DOI: 10.1186/s41479-017-0040-3
|View full text |Cite
|
Sign up to set email alerts
|

Case report on a defective antibody response against pneumococcal serotype 9V in a patient with a single episode of pneumonia

Abstract: BackgroundPatients with recurrent respiratory tract infections and an impaired response to pneumococcal polysaccharide vaccination are diagnosed with a specific antibody deficiency. In adult patients with pneumococcal pneumonia an impaired antibody response to the infecting pneumococcal serotype can sometimes be found. It is unknown whether these patients are unable to produce an adequate anti-polysaccharide antibody response to pneumococcal vaccination after recovery.Case presentationThe authors describe a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Likewise, the impaired immune response observed in the current study might also have been influenced by exposure to a high level of circulating CPS, either during previous colonization or infection or during the studied CAP episode. This is in line with previous studies that suggest an association between antigenemia and a poor quantitative Ig response ( 8 , 10 ). Moreover, we found that the two patients with the highest pneumococcal DNA concentration in plasma (see Table S1 in the supplemental material) exhibited nonfunctional convalescent-phase responses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Likewise, the impaired immune response observed in the current study might also have been influenced by exposure to a high level of circulating CPS, either during previous colonization or infection or during the studied CAP episode. This is in line with previous studies that suggest an association between antigenemia and a poor quantitative Ig response ( 8 , 10 ). Moreover, we found that the two patients with the highest pneumococcal DNA concentration in plasma (see Table S1 in the supplemental material) exhibited nonfunctional convalescent-phase responses.…”
Section: Discussionsupporting
confidence: 93%
“…Few previous studies on the dynamics of naturally acquired pneumococcal immunity related to an infection episode exist. An association of pneumococcal antigenemia with an attenuated convalescent-phase quantitative anti-CPS Ig response was, however, reported in 1976 ( 8 ), and decreased serotype-specific Ig concentrations following pneumococcal infection have been described in case reports ( 9 , 10 ). In one previous study ( 24 ), 88% of convalescent-phase sera from patients with nonbacteremic pneumonia had functional opsonic Ig compared to 50% of sera from bacteremic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few previous studies on the dynamics of naturally acquired pneumococcal immunity related to an infection episode exist. An association of pneumococcal antigenemia to an attenuated convalescent-phase quantitative anti-CPS Ig response was, however, already reported in 1976 (8), and decreased serotype-specific Ig concentrations following pneumococcal infection have been described in case reports (9,10). In one previous study (24), 88% of convalescent-phase sera from patients with nonbacteremic pneumonia had functional opsonic Ig, compared to 50% of sera from bacteremic patients.…”
Section: Discussionmentioning
confidence: 91%
“…Episodes of asymptomatic nasopharyngeal colonization induce protective adaptive immunity, but studies on the dynamics of naturally acquired immunity related to episodes of clinically significant pneumococcal infection are scarce (7). Interestingly, a delayed or absent anti-CPS Ig increase has been described after pneumococcal bacteremia (8)(9)(10). This observation raises the question of whether infection by pneumococci, unlike with an episode of asymptomatic colonization, may fail to induce immunologic boosting.…”
mentioning
confidence: 99%